1968
DOI: 10.1083/jcb.39.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Biochemical Characterization of Goldfish Erythrophores and Their Pterinosomes

Abstract: The fine structure of integumental erythrophores and the intracellular location of pteridine and carotenoid pigments in adult goldfish, Carassius auratus, were studied by means of cytochemistry, paper and thin-layer chromatography, ionophoresis, density-gradient centrifugal fractionation, and electron microscopy. The ultrastructure of erythrophores is characterized by large numbers of somewhat ellipsoidal pigment granules and a well-developed system of tubules which resembles endoplasmic reticulum. The combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…Ultrastructural observations revealed that the erythrophoroma cells were characterized by numerous large spherical cytoplasmic particles (0.4-0.7 ;/m in diameter) (Fig 3) [5,6], which were identical to the pterinosomes seen in normal erythrophores and regarded as specific pigment granules [7]. In addition to pterinosomes, many well-developed, tubular, smooth endoplasmic reticulum in the crythrophoroma cells were found.…”
Section: Smentioning
confidence: 99%
“…Ultrastructural observations revealed that the erythrophoroma cells were characterized by numerous large spherical cytoplasmic particles (0.4-0.7 ;/m in diameter) (Fig 3) [5,6], which were identical to the pterinosomes seen in normal erythrophores and regarded as specific pigment granules [7]. In addition to pterinosomes, many well-developed, tubular, smooth endoplasmic reticulum in the crythrophoroma cells were found.…”
Section: Smentioning
confidence: 99%
“…As seen in the above description, a similarity exists in the morphological charactersitics between the melanosomes and pterinosomes. As a biochemical similarity, tyrosinase was found in the pterinosomes of the frog, Rana japonica (14), a teleostean fish, Oryzias latipes ( 5 ) and the goldfish (9,6). The present biochemical study, which is concerned with the adult xanthophores, asks several questions.…”
mentioning
confidence: 99%
“…It was also suggested that the dispersion of carotenoids does not involve the release of pigment from, but rather the movement of, the SER (Winchester et al, 1976), yet lipid monolayers surrounding carotenoid droplets were found within such SER cisternae . Thin-section TEM results also suggested that carotenoids might be transported within the agranular reticulum in goldfish erythrophores (Matsumoto and Obika, 1968). Hormone-induced dispersion of CD and SER was inhibited by cytochalasin B in primary cultures of xanthophores, as well (Obika et al, 1978b).…”
Section: Goldfish Xanthophores Early Studies: Thin-section Tem Workmentioning
confidence: 93%